EP967 Natural history of patients with BRCA-mutated high grade epithelial ovarian cancer (HGEOC) before the era of PARP inhibitors maintenance in 1st line treatment. (1st November 2019) - Romeo, C; Meeus, P; Rodrigues, M; Leblanc, E; Floquet, A; Pautier, P; Marchal, F; Provansal, M; Campion, L; Causeret, S; Gourgou, S; Ray-Coquard, I; et al.
Abstract : Introduction/Background: In SOLO1 trial, maintenance therapy with olaparib considerably improved progression-free survival (PFS) among women with newly-diagnosed, advanced BRCA-mutated HGEOC. Based on the large real-life ESME ovarian cancer (OC) cohort, we aimed to describe the patient's characteristics and survival outcomes of a selected cohort of BRCA-mutated patients before the era of PARP inhibitors maintenance in first line. Methodology: ESME OC is a national cohort including all patients (pts) with EOC managed in the 18 French Comprehensive Cancer Centres (NCT03275298 ). ESME Research program collected retrospective data from patient's medical records. BRCA1, BRCA2, or both mutated patients with de novo diagnosed advanced (FIGO stage III or IV) high-grade serous or endometrioid EOC were eligible. Primary objective was to describe patient's characteristics, clinical features and treatment patterns. Results: Of the 4777 patients with OC treated in first line by platinum-based chemotherapy between 2011 and 2016, 266 were included. Median age was 57.0 (33–81). 187 pts (70.3%) harbored a BRCA1 mutation, and 75 (28.2%) a BRCA2 mutation. 66.9% of patients had FIGO stage III disease. Almost all patients (95.5%) underwent surgical resection, after neoadjuvant chemotherapy (48%), or primary debulking surgery (44.9%). 119 pts (44.7%) received maintenance therapy and majority with bevacizumab alone (78.9%). After a median follow-up of 51.7months, the median PFS (mPFS) was 28.6months [95 CI: 26.2–32.4]. Patients exhibited higher mPFS in case of FIGO stage III than stage IV (32.4 months and 25.4 months, respectively), or BRCA2 mutation than BRCA1 (33.3 months and 27.7 months, respectively). Although populations were non comparable, mPFS was close between patients treated with or without maintenance (28.3 and 29.5 months, respectively). Median PFS2 were 51.4 months and 50.4 months, respectively. Estimated 5-year OS for the whole population was 69.2% [95 CI: 65.3–73.0]. Conclusion: This large ESME OC cohort described clinical features and real-life survival outcomes among pts with newly diagnosed advanced BRCA-mutated HGEOC treated in specialized centres. Disclosure: This work was supported by UNICANCER. The ESME OC database is supported by an industrial consortium (Roche, Pfizer, AstraZeneca, MSD, Eisai and Daiichi Sankyo). Data collection, analyses and publications are totally managed by R&D UNICANCER independently of the industrial consortium. All the authors declare that there is no conflict of interest regarding the publication of this article.